Collector’s grandmother in the garden where she often finds designs for her mats, with view of her home in the background - White, Loretta (1979)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Oral History - Creative Crafts ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Oral History - Creative Crafts"